A high-resolution bedrock map for the Antarctic Peninsula - Huss, Matthias; id_orcid:0 000-0002-2377-6923; Farinotti, Daniel; id_orcid:0 000-0003-3417-4570 (Copernicus, 2014)
Assessing and projecting the dynamic response of glaciers on the Antarctic Peninsula to changed atmospheric and oceanic forcing requires high-resolution ice thickness data as an essential geometric constraint for ice flow models. Here, we derive a complete bedrock data set for the Antarctic Peninsula north of 70° S on a 100 m grid. We calculate distributed ice thickness based on surface topography and simple ice dynamic modelling. Our approach is constrained with all available thickness measurements from Operation IceBridge and gridded ice flow speeds for the entire study region. The new data set resolves the rugged subglacial topography in great detail, indicates deeply incised troughs, and shows that 34% of the ice volume is grounded below sea level. The Antarctic Peninsula has the potential to raise global sea level by 69 ± 5 mm. In comparison to Bedmap2, covering all Antarctica on a 1 km grid, a significantly higher mean ice thickness (+48%) is found. ISSN:1994-0416 ISSN:1994-0424